Quantifying Student Satisfaction: Teaching Quality, Infrastructure, and Support Services - Gautam, Tara Prasad; Shailashri, V T; Mishra, Shila (New Perspective: Journal of Business and Economics, 2025)
Student satisfaction is the main indicator of higher quality of education since it also affects academic performance, institutional reputation, and student retention. This study rigorously evaluates student satisfaction in community colleges of Bagmati Province, Nepal, in respect to infrastructure, institutional support systems, and teaching quality. A descriptive cross-sectional study design was applied and 400 undergraduate and postgraduate students responded to a survey to assess their perceptions of significant academic and institutional aspects. Data were analyzed using descriptive statistics (mean, median, standard deviation) and inferential techniques. The results show that strong faculty-student interaction and good classroom delivery are revealed as positives; yet, the results also highlight problems with reference to research opportunities, practical skill development, and student support services. Infrastructure-related problems including restricted library resources, poor digital learning tools, and inadequate sanitation and cafeteria facilities constitute major areas needing attention. Students expressed dissatisfaction with career advising help, scholarship transparency, and grievance management mechanisms even while administrative services and communication got high grades. The study suggests extending experiential learning, upgrading digital resources, enhancing research efforts, and increasing institutional governance in order to enhance student satisfaction and academic excellence. These findings support the more general discussion on quality assurance in Nepalese higher education and offer useful guidance to institutional leaders and legislators aiming at continuous progress.